Affective predictors of the severity and change in eating psychopathology in residential eating disorder treatment: The role of social anxiety. Issue 1 (2nd January 2018) - Smith, Kathryn E.; Mason, Tyler B.; Leonard, Rachel C.; Wetterneck, Chad T.; Smith, Brad E. R.; Farrell, Nicholas R.; Riemann, Brad C.
ABSTRACT: Despite evidence documenting relationships between eating disorder (ED) psychopathology, depression, and anxiety, little is known regarding how social anxiety is related to ED symptoms in treatment. Therefore this study examined associations between depression, general anxiety, social anxiety, and ED psychopathology at the beginning and end of treatment (EOT) among patients ( N  = 380) treated in a residential ED program. Participants completed measures of ED psychopathology and affective variables. Higher depression and general anxiety, but not social anxiety, were related to higher ED psychopathology at baseline. However, social anxiety emerged as a unique predictor of ED psychopathology at EOT such that participants with higher social anxiety evidenced less improvement in ED psychopathology. Findings suggest that social anxiety has specific relevance to treatment in EDs, which may reflect shared mechanisms and underlying deficits in emotion regulation.